Nonlinear behaviour in flexible, large-scale space structures: dynamics and control - Elliott, Alex J.; Felicetti, Leonard (Springer, 2024)
Large-scale structures are becoming increasingly common for space applications, driven by advances in in-orbit manufacturing and construction, lightweight materials, and robotics. While these structures have the potential to be key enablers for the next generation of space applications—see, for example, recent interest in space-based solar power—their ability to deliver such goals depends on the stability and controllability of their dynamics. Large-scale space structures, which often have architectures at the kilometre length scale, face several important dynamic challenges. In this work, we propose a novel control strategy for flexible satellites based on a dual unscented Kalman filter strategy. The methodology is outlined and then applied to a smaller satellite, which is assumed to be linear. A key aim of this research is the accurate identification of the moment of inertia of the system, which we demonstrate the methodology can achieve within 1% (or significantly closer), even when the initial assumptions are inaccurate. Finally, we discuss the implications for larger structures, and how the work will be expanded in the future.
Keywords: 3403 Macromolecular and Materials Chemistry; 40 Engineering; 34 Chemical Sciences; Nonlinear Vibrations; Control; Attitude and Orbit Dynamics; Flexible Satellites; Kalman Filters